2022
DOI: 10.3389/fmicb.2022.855859
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and Evolutionary Implications of Microbial Dispersal

Abstract: Dispersal is simply defined as the movement of species across space and time. Despite this terse definition, dispersal is an essential process with direct ecological and evolutionary implications that modulate community assembly and turnover. Seminal ecological studies have shown that environmental context (e.g., local edaphic properties, resident community), dispersal timing and frequency, and species traits, collectively account for patterns of species distribution resulting in either their persistence or un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 146 publications
(166 reference statements)
0
52
0
Order By: Relevance
“…However, deterministic processes (homogeneous and heterogeneous selections) also contributed considerably to shaping rare subcommunity assembly. For microbial dispersal, passive dispersal is one of the common mechanisms (Ai et al, 2013 ; Custer et al, 2022 ), which is mediated by wind and rain or by hitchhiking on other organisms and could be easily influenced by physical barriers, such as mountains (Prosser et al, 2007 ; Jia et al, 2018 ; Mestre and Höfer, 2021 ). The Qinghai-Tibet Plateau is influenced by the East Asian monsoon, Indian monsoon, and continental westerlies (He et al, 2020 ), which can carry a variety of microorganisms and disperse across the QTP (Xing et al, 2021 ; Qi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, deterministic processes (homogeneous and heterogeneous selections) also contributed considerably to shaping rare subcommunity assembly. For microbial dispersal, passive dispersal is one of the common mechanisms (Ai et al, 2013 ; Custer et al, 2022 ), which is mediated by wind and rain or by hitchhiking on other organisms and could be easily influenced by physical barriers, such as mountains (Prosser et al, 2007 ; Jia et al, 2018 ; Mestre and Höfer, 2021 ). The Qinghai-Tibet Plateau is influenced by the East Asian monsoon, Indian monsoon, and continental westerlies (He et al, 2020 ), which can carry a variety of microorganisms and disperse across the QTP (Xing et al, 2021 ; Qi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microbial biogeography has been studied mainly in relation to environmental filtering (e.g., by lake chemistry), yet dispersal has become an increasingly popular topic for microbial research (Custer et al, 2022). Despite early work with microscopic algae, the lack of studies of microbial dispersal by waterbirds was clear in the earlier review of Figuerola and Green (2002), and the relative lack of recent research is evident from the resulting citations (Figure 2).…”
Section: Understudied Role Of Waterbirds As Vectors For Microbesmentioning
confidence: 99%
“…We found that eleven candidate-core taxa were not represented in field-grown plants, which could result from a range of factors. For example, glasshouses may physically limit the dispersal of environmental microbes [84], particularly from aerial sources, which may explain why the alpha diversity of above-ground compartments in field-grown plants was larger than in our potted plants (Additional file 1: Fig. S6).…”
Section: Musa Spp Microbiomes Differ Between Soils Immature Pot Plant...mentioning
confidence: 99%